Genetic evaluation of Ethiopian Boran cattle and their crosses with Holstein Friesian for growth performance in central Ethiopia - Haile, Aynalem; Joshi, B.K.; Ayalew, W.; Tegegne, T.; Singh, A. (Wiley, 2011)
Breed additive and non-additive effects, and heritabilities of birth weight (BWT), weaning weight (WWT), 6 months weight (SMWT), yearling weight (YWT), eighteen months weight (EWT), 2 years weight (TWT) and average daily weight gain from birth to 6 months (ADG1) and from 6 months to 2 years (ADG2) were estimated in Ethiopian Boran (B) cattle and their crosses with Holstein Friesian (F) in central Ethiopia. The data analysed were spread over 15 years. Ethiopian Boran were consistently lighter (p < 0.01) than the B-F crosses at all ages. Ethiopian Boran also gained lower weight than all the crosses. At birth, 50% F crosses were significantly (p < 0.01) lighter than all the other crosses. However, the differences in SMWT, YWT, EWT, TWT, ADG1 and ADG2 were all non-significant among the crosses. The individual additive breed differences between B and F breeds were positive and significant (p < 0.01) for all traits. The individual heterosis effects were significant (p < 0.05) for all traits except WWT for which the effect was non-significant. The maternal heterosis effects were significant (p < 0.01) for BWT (2.5 kg) and WWT (−3.0 kg). The heritability estimates for all traits in B and crosses were generally moderate to high indicating that there is scope for genetic improvement through selection. Selection within B and crossbreeding should be the strategy to enhance the growth performance under such production systems.